The Atlantic granulite belt, Brazil. - Wernick, E. (My University, 1981)
The low- to medium-P Atlantic granulite belt was largely formed at 2700 m.y., but 3100 m.y. ages have been obtained from the granulite belt and adjacent craton. -J.A.H.